Postpartum Depression Screening for New Mothers at Well Child Visits. Issue 3 (May 2018) - Emerson, Margaret R.; Mathews, Therese L.; Struwe, Leeza
Abstract: Background: Postpartum depression (PPD) is a debilitating emotional experience that can affect mothers and their infants. Screening for PPD is encouraged during pediatric well-child visits (WCVs); however, the frequency, referral process, and documentation relative to screening in clinical practice require further study. Objectives: There were three purposes to this study: 1) determine prevalence of mothers who scored in the at-risk range using the Edinburgh Postnatal Depression Scale (EPDS) at each of the 2-, 4-, and 6-month WCVs in a pediatric outpatient practice; 2) examine feasibility factors relative to extending the current standard of care for PPD screening; and 3) examine visit documentation for at-risk mothers. Design: A prospective cohort study design was used to screen mothers during their infants' 6-month WCV for PPD using the EPDS. Feasibility in adding the 6-month time frame was assessed using an investigator-designed clinical team survey. Visit documentation content was obtained through medical record review. Results: Forty-three postpartum women were included in the study. Prevalence rates among participants were 10%, 12.5%, and 14% for 2-month, 4-month, and 6-month WCVs, respectively. The clinical team found the additional screening at the 6-month visit to be feasible. Documentation for mothers identified to be at-risk varied greatly.Conclusions: Prevalence of PPD among participants is consistent with previously reported rates. Areas identified for improved clinical practice include the content of the visit that is documented in the medical record and reviewed with mothers identified to be at-risk, time allotted for the clinical team to screen new mothers, and appropriate referral to outside sources. Abstract : Pediatric well child visits offer an opportunity to screen new mothers for postpartum depression. This study examines the feasibility of screening for postpartum depression in the pediatric ambulatory setting, the content of the discussion about postpartum depression with the new mother and the pediatric provider, and prevalence of postpartum depressions among study participants.